A case-control study of the congenital hypothyroidism and dysmaturity syndrome of foals. - Allen, A L (1996)
A case-control study was conducted to identify risk factors for the congenital hypothyroidism and dysmaturity syndrome of foals. A questionnaire was used during personal interviews of foal owners and farm managers to collect information on animal signalment, farm environment, and mare management. Information on 39 foals with the congenital hypothyroidism and dysmaturity syndrome were compared with 39 control foals. Foals with the syndrome had a significantly (P < 0.0001) longer gestation (357.6 d) than control foals (338.9 d). Pregnant mares that were fed greenfeed, did not receive any supplemental mineral, left their "home farm" during gestation, or grazed irrigated pasture had 13.1 (P = 0.0068), 5.6 (P = 0.0472), 4.3 (P = 0.0076), and approximately 15.3 (P = 0.0245), respectively, greater odds of producing an affected foal than mares not experiencing these events. Greenfeed often contains high levels of nitrate (NO3-), which is known to impair thyroid gland function. In light of this, forage samples from participating farms were analyzed for nitrate levels. The odds of one or more congenitally hypothyroid and dysmature foals being born on a farm feeding forage with at least a trace of nitrate was 8.0 times greater (P = 0.0873) than the odds of the disease occurring on a farm that fed forage free of nitrate. Further, the odds of a mare producing an affected foal when fed forage containing at least a trace of nitrate were 5.9 times greater (P = 0.0007) than those of a mare fed nitrate free forage. This study suggests that congenital hypothyroidism and dysmaturity syndrome in foals may be the result of diets that contain nitrate or that are low in iodine being fed to pregnant mares.